PROGRAM KHURUJ JAMAAH TABLIGH DALAM PERSPEKTIF MAQASID AL-SYARI‘AH - Nilhakim (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
Khuruj is one of the teachings in Jama'ah Tabligh which requires each member to go outside the area to broadcast amr al-ma`ruf nahy al-munkar within a certain time. They go out for 3 days a month, 40 days a year, and 4 months in a lifetime. The main problem is when the obligation khuruj faced with obligations in the family. Such obligations can cause problems when members of Jama'ah Tabligh can’t balance the obligation to the family in performing khuruj. On the other hand, it is very unfortunate that the lack of coordination and evaluation of care among families of members of the congregation so as to cause negative effects from the community that the tabligh worshipers less attention to families left behind. Therefore, this khuruj program should be studied with the approach of usul al-fiqh (maqasid al-syari'ah), how is khuruj allowed according to syara '. The method used in the study of the analysis conducted by looking at the benefits and harm. Based on this study, it is concluded that khuruj is a real step in the spread of Islamic syiar that not all Islamic organizations are able to implement it. However, the problem of abandoned family requires good coordination in the family, so if the members of Jamaah Tabligh do khuruj must be with the preparation of checking (family must be examined readiness related to intention, stock, physical and family to be left behind) become main and obligatory before doing khuruj so Harm can be rejected.